PERAN DEWAN PENGAWAS SYARIAH DALAM MELAKUKAN PENGAWASAN TERHADAP PELAKSANAAN AKAD PADA LEMBAGA PEMBIAYAAN SYARIAH (Studi Terhadap FIF Syariah Cabang Pontianak) - MUJAHID, S.HI, A.21212065, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
ABSTRACTFederal International Finance Sharia (FIF Sharia) is a one of non-Islamic financial institutions which form of Limited Liability Company and in accordance with applicable regulations FIF Sharia is also have the Sharia Supervisory Board as well as the completeness of its operations to ensure the performance of Islamic finance company is run in accordance with Islamic principles . To view and to determine the extent the performance of the Sharia Supervisory Board in overseeing the implementation of the agreement in FIF Syaraiah, it is necessary to research on